Poly(3-hydroxybutyrate): Promising biomaterial for bone tissue engineering - Dariš Barbara; Knez Željko (Acta Pharmaceutica)
Poly(3-hydroxybutyrate) is a natural polymer, produced by different bacteria, with good biocompatibility and biodegradability. Cardiovascular patches, scaffolds in tissue engineering and drug carriers are some of the possible biomedical applications of poly(3-hydroxybutyrate). In the past decade, many researchers examined the different physico-chemical modifications of poly(3-hydroxybutyrate) in order to improve its properties for use in the field of bone tissue engineering. Poly(3-hydroxybutyrate) composites with hydroxyapatite and bioglass are intensively tested with animal and human osteoblasts in vitro to provide information about their biocompatibility, biodegradability and osteoinductivity. Good bone regeneration was proven when poly(3-hydroxy-butyrate) patches were implanted in vivo in bone tissue of cats, minipigs and rats. This review summarizes the recent reports of in vitro and in vivo studies of pure poly(3-hydroxy-butyrate) and poly(3-hydroxybutyrate) composites with the emphasis on their bioactivity and biocompatibility with bone cells.